PETROLOGI DAN STRUKTUR GEOLOGI DAERAH PANAS BUMI CITANDO BANTEN - Anggi Anggi Deliana S; Hari Wiki Utama (Prodi Fisika FST UNJA, 2020)
The appearance geothermal features on the Citando Banten is a indication of geothermal system. Hot spring manifestation on Miocene Cimapang sandstone and Pliocene andesite intrusion become guideline, there is diffirence of geothermal system. For understanding its needed study of petrology and structural geology. Petrology study with petrography analysis for some sample on the appearance of geothermal manifestation and also some sample on the volcanic complex, its Southeastern of geothermal features. Structural geology is role of important for knowing of control fracture characterics of appearance geothermal features of the Citando Area. Petrography of andesit is composed of andesine plagioclase, clinopyroxene, hornblende, and groundmass. Its sndesit shallow intrusion has probably the role of heat transfer. Sandstone compiled by quartz, lithic, hornblende, plagioclase as fragment with mud supported, wich alteration intensity is low relative. Product of volcanic complex features is andesitic lava, its composed of andesine plagioclase, clinopyroxene, hornblende, groundmass with pilotaxitic texture. Tuff and lapilli tuff as pyroclastic product with mineral composition of volcanic glass, lithic fragmen, and quartz.the presence of volcanic rock as a indication there is strato volcanic complex near to appearance of geothermal manifestation. Structural geology between of sinistral fault which is orientation North-Northeastern - South-Southeastern as major fault the directly related to appearance geothermal manifestation and also its recorded of volcanic complex, cutting thrust fault which Western - Eastern direction relatively, dextral fault as young fault which is Northwestern - Southeastern has cutting major fault. The appearance of geothermal manifestation on manjor fault is indication its facilitating or pathway of surface gothermal features, and also cutting of Cimapang sandstone-claystone anticline and assured as younger fault the volcanic complex formation. The features of petrology and structural geology, the appearance geothermal manifestation have connection to volcanic complex part of Southeastern geothermal manifestation.